2017
DOI: 10.1038/sc.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization in persons with spinal cord injury: part 1—outpatient services

Abstract: Individuals with SCI are frequent users of medical services. There is no group of medical specialists that covers all needs of persons with SCI, what emphasizes health care provision from a comprehensive perspective including a wide array of services. Instances with care required but not received appeared to be rare and more likely in participants with migration background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 20 publications
1
55
1
Order By: Relevance
“…The current findings reinforce previously reported barriers for people with SCI such as inadequate transport systems and limited local community infrastructure 6,7 ; inflexible, inadequate and inappropriately skilled personal care 6,8 ; limited generalist services combined with geographically distant specialist services 9‐11 ; as well as restricted and inflexible GP services and allied health services 12‐14 . Participants voiced the need for councils, personal care agencies, transport providers and health care systems to make changes to reduce these challenges yet recognised the economic pressures preventing such change.…”
Section: Discussionsupporting
confidence: 81%
“…The current findings reinforce previously reported barriers for people with SCI such as inadequate transport systems and limited local community infrastructure 6,7 ; inflexible, inadequate and inappropriately skilled personal care 6,8 ; limited generalist services combined with geographically distant specialist services 9‐11 ; as well as restricted and inflexible GP services and allied health services 12‐14 . Participants voiced the need for councils, personal care agencies, transport providers and health care systems to make changes to reduce these challenges yet recognised the economic pressures preventing such change.…”
Section: Discussionsupporting
confidence: 81%
“…This is especially important for countries with poorly developed or fragmented rehabilitation systems. As individuals with SCI are frequent users of rehabilitation and other health services, 28,29 they will be more directly impacted by difference in the performance of health systems. As more fully discussed in an article in this issue, "Comparison of the Social Response to Functioning Needs of People With SCI Across Over 20 Countries," InSCI data can provide evidence for standard socioeconomic indicators that can serve as performance indicators of health systems, as applied to persons with SCI.…”
Section: Main Outcomesmentioning
confidence: 99%
“…Good access to appropriate health care seems to play such an important role in the lives of people with SCI that they are willing to choose their residential location based on the availability of appropriate health care. This is interesting, particularly since the health care supply in Switzerland is generally high and a doctor is never really far away regardless of where a person lives (4.0 physicians per 1000 residents; 99.8% of the population reaches a general hospital by car within 30 min, 94.0% within 15 min; 75% reach a specialized SCI center within 75 min) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides living close to highly specialized SCI centers, it also seems important to people with SCI to have a wide array of outpatient services nearby. People with SCI rely on various outpatient services [ 28 ] which they use much more frequently than the general population [ 34 , 35 ]. The current study has demonstrated a positive correlation between the density of outpatient physicians practicing in a region and the propensity of people with SCI to live there.…”
Section: Discussionmentioning
confidence: 99%